HUBUNGAN GENDER DAN ETNISITAS : BEBERAPA KASUS DI DUNIA KETIGA - Santoso, Widjajanti M (P2KK LIPI, 2003)
The article is a description of several cases about third world women in changing situation. The women experience political conflict or migration to other places, therefore problem of identity become an important subject. As a general social context, identity is important as society becomes heterogenous. To some extent, this context give opportunities for women to participate in public sphere. Whereas women has gained more space in public, there are always a movement to hold them back in their privat sphere. This is a specific problem of third world women, whether in their countries or in other countries.